Effects of different tillage systems and planting densities on soil physical properties and yield components of sweet corn (Zea mays L.) - Shamsabadi, Hosseinali Tash (2011)
Sweet corn or maize (Zea mays L.) is the world’s most important crops after wheat, barley and rice. This plant is nutritionally superior to other cereals in many ways, except in protein value. Considering the limitation of production resources and the increasing world population, efforts should be made to increase productivity of crop. Among the factors that influence corn productivity are planting density and tillage practices. In Malaysia, the rotary cultivator method which has been the common practice for sweet corn has some disadvantages and it would be worthwhile to compare it with other tillage methods. The shallow depth of ploughing and degradation of the soil because of intensive impact of the rotary blade with the soil has been identified as problems of this tillage method. The main objective of this study was to find out the best tillage system or method in terms of soil physical characteristics, and then determining the crop yield of sweet corn as affected by different planting densities. In addition, the most economical tillage system in the field, optimum energy on drawbar power and engine fuel consumption for three tillage methods were also calculated. Field experiments were conducted over two years (2008 and 2009) to investigate the effects of three tillage systems on selected soil physical properties at two depths of 0-15 and 20-35 cm in the Serdang series soil (Typic Paleodult). The research farm was located in the University Putra Malaysia (UPM) in Malaysia. It was under continuous corn planting for several years. The three tillage systems or methods were Moulboard Plough followed by once tandem disc harrowing (MPD), Disc Plough followed by once tandem disc harrowing (DP) and Rotary Cultivator only (RC) as control. Soil physical properties were measured two times, before and after soil tillage and included bulk density dry basis (BDd), total porosity (Pt), aggregate size distribution (Aggd≥2mm), mean weight diameter dry basis and wet basis (MWDd and MWDw), water infiltration (WI), moisture content volume basis (MCv) and resistance to penetration (RP). At the end of the experiment, energy and fuel consumption utilized on the soil ploughed by the tillage systems were calculated. The results showed that the measured soil physical properties at two depths of the plots (before tillage operation) were homogeneous at three plots and two depths. The highest value of crop yield at any given planting density occurred in MPD plot and decreased in DPD and RC plots, respectively in 2008 and combined two years. This result could be due to lower BDd and Aggd≥2mm, higher MWDw and Pt in upper layer (0-15 cm) for MPD plot. However WI was higher and RP was lower in RC plot at the same depth. The other reason for sweet corn reduction in RC plot could be higher BDd and RP at the depth of 20-35 cm that impeded root growth of sweet corn; however MCv was higher in lower layer. Depth of soil tillage by RC (15 cm) and creation of plough-pan below this depth (plough layer) was the other reason for the lower yield under RC. Tillage method, planting density and also interaction effects of two factors, tillage and planting density were found to be significant on yield and some yield components of sweet corn such as ear diameter, row length of the kernels on the cob corn, fresh weight of ear con, yield of sweet corn and total weight of dry matter, in 2008. Similarly, all yield parameters except for ear diameter were affected by planting density and interaction of the two factors in 2009. Irrespective of planting density, corn yield was lowest in RC tillage in 2008 and for the combined two years. Crop yield with DPD was 8% higher than RC and with MPD it was 20% higher than RC. Ear diameter, row length of kernel on cob corn and weight of ear were higher at low density compared to high density planting. This could be due to the lower stress or competition between the plants for moisture, nutrients and sunlight under low density planting. Although the stress was higher for the plants with seed spacing of 20 cm; however it did not affect the crop yield and total weight of dry matter at any given tillage methods. This result revealed that there was no deficit of moisture and nutrients for the plants close to each other. Only the limitation of sunlight could be the reason for this finding. Climate or weather condition in 2009 was better than 2008 in terms of greater rainfall and sunshine hour. That is why the yield and some yield components of sweet corn were better in 2009 as compared to 2008 for DPD and RC plot. Energy consumption on drawbar power was higher on the soil ploughed with DPD was 56.2 hp and decreased with MPD (52.5 hp) and RC (45.5 hp), respectively whilst fuel consumption was higher on the soil ploughed with MPD (27.02 L) and decreased to 25.69 L with DPD and 18.04 L with RC, respectively. Although energy on drawbar power and engine fuel consumption were higher under MPD and DPD tillage treatments as compared to RC, there was greater benefit gained in MPD plot (20%) and DPD plot (8%) respectively. On the other hand, the highest profit was obtained in MPD plot (RM 21,600) and this decreased to RM 19,500 in DPD plot and RM 18,100 in RC plot, respectively. In general, working condition of two tillage methods (MPD and DPD) was similar in trend in terms of soil physical properties, yield and its components of sweet corn. However, mouldboad plough to a depth of 25 cm followed by one time tandem disc harrowing to a depth of 10 cm with seed spacing of 20 cm showed the best overall results in terms of yield and economic benefit.